2015
DOI: 10.1093/jjco/hyv022
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the responses to pazopanib and the prognoses of soft tissue sarcomas by their histological eligibility for the PALETTE study

Abstract: Objective: In Japan, pazopanib has been made available to soft tissue sarcoma patients, also to patients histologically diagnosed as ineligible for the international Phase 3 study (PALETTE). However, clinical evidence for the use of pazopanib in PALETTE-ineligible patients is currently insufficient. Methods: We retrospectively reviewed medical records of soft tissue sarcoma patients treated with pazopanib at our institute. By pathological review, the patients' eligibility for the PALETTE study was evaluated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
(12 reference statements)
3
9
0
Order By: Relevance
“…Thirdly, PALETTE ineligible patients with histology such as embryonal rhabdomyosarcoma, liposarcoma and Ewing’s sarcoma were included on the trial. In addition a recent study by Nakano et al notes that PALLETTE study ineligible patients might have worse prognosis on pazopanib than PALETTE-eligible patients and our study confirms this (24). The resistance mechanisms to VEGF inhibitors such as pazopanib are complex.…”
Section: Discussionsupporting
confidence: 90%
“…Thirdly, PALETTE ineligible patients with histology such as embryonal rhabdomyosarcoma, liposarcoma and Ewing’s sarcoma were included on the trial. In addition a recent study by Nakano et al notes that PALLETTE study ineligible patients might have worse prognosis on pazopanib than PALETTE-eligible patients and our study confirms this (24). The resistance mechanisms to VEGF inhibitors such as pazopanib are complex.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, when choosing an anticancer drug for second-line treatment of liposarcoma and leiomyosarcoma, in addition to the clinical evidence, safety issues such as the onset or worsening of cardiac dysfunction caused by doxorubicin should be considered. Furthermore, retrospective studies from Japan have shown the inferior efficacy of pazopanib in the treatment of liposarcoma compared with other subtypes [35, 36]. Ifosfamide can also be an option for second-line and later treatment for metastatic STS, especially in cases of fibrosarcoma and synovial sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an interruption or reduction of pazopanib was required in 10 patients because of thrombocytopenia. Nakano et al reported that 28% of Japanese patients with STS (13 of 47 patients) developed grade 1 or 2 thrombocytopenia, although there were no patients who required an interruption or reduction of pazopanib treatment . Physicians should be alert to the occurrence of pneumothorax and thrombocytopenia as well as other well known adverse events.…”
Section: Discussionmentioning
confidence: 99%